2003
DOI: 10.1097/00007632-200301150-00021
|View full text |Cite
|
Sign up to set email alerts
|

Horner’s Syndrome Caused by a Thoracic Dumbbell-Shaped Schwannoma: Sympathetic Chain Reconstruction After a One-Stage Removal of the Tumor

Abstract: A mediastinal dumbbell-shaped schwannoma has rarely been described as a cause of Horner's syndrome. Primary sympathetic nerve reconstruction with an intercostal nerve was shown to be useful after resection of the sympathetic nerve involved in the tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 19 publications
0
12
1
1
Order By: Relevance
“…Telaranta reported that reconstruction of the sympathetic chain using sural nerve graft diminished compensatory sweating in a male patient who underwent sympathicotomy for palmar hyperhidrosis (20). Miura et al (21) reported that sympathetic nerve reconstruction surgery using the intercostal nerve was useful after resection of the sympathetic nerve involved by tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Telaranta reported that reconstruction of the sympathetic chain using sural nerve graft diminished compensatory sweating in a male patient who underwent sympathicotomy for palmar hyperhidrosis (20). Miura et al (21) reported that sympathetic nerve reconstruction surgery using the intercostal nerve was useful after resection of the sympathetic nerve involved by tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, a plethora of different lesions have been described, including a chordoma,5 thymic cyst,6 hydatid cyst,7 bronchogenic cyst,8 aneurysmal bone cyst9 and seven cases of benign intrathoracic schwannoma causing HS 10–16. Of these cases, the nerve of origin was judged to be a sympathetic nerve in three cases,10 12 15 the first thoracic nerve in one case11 and an intercostal nerve in another case 13. In this case, the enormous size of the tumour made it exceedingly difficult to identify the nerve of origin.…”
Section: Discussionmentioning
confidence: 95%
“…The vast majority are benign neurogenic tumours, of which schwannomas account for around 90%. [1][2][3] The presenting history is usually unremarkable and non-specific; local and radicular pains are typical presenting features. 4 Optimal surgical approach of these tumours remains a debatable topic with different authors advocating competing strategies.…”
Section: Discussionmentioning
confidence: 99%